Study of Relative Antioxidant Potential of Induced Variants of Catharanthus roseus (L.) G. Don in Salt Stress Condition for the Effective Selection of Salt Tolerant Variant - Verma, Ashutosh Kumar (Free Radicals and Antioxidants)
Objectives: Catharanthus roseus (L.) G. Don is an important plant documented for variety of medicinal uses and salt tolerant potential. During genetic improvement programme an attempt of induced mutagenesis was made for isolation of improved genotype of C. roseus var. Nirmal (CIMAP 0865) and nine EMS induced variants were isolated. Present study was made for the assessment of relative antioxidative potential of these variants and identification/selection of salt tolerant genotype. Methods: For the assessment of relative antioxidative potential under glass house condition one month old seedlings of all variants exposed to salt stress condition and the activities of antioxidant enzymes viz., superoxide dismutase, peroxidase and catalase were estimated in leaf tissue at 4th day and 8th day of NaCl supply while proline and total alkaloid contents were estimated at 8th day of NaCl supply. Results: In general, NaCl imposition causes increase in activity of earlier two enzymes, decrease in catalase activity and stimulatory effect on proline and total alkaloid content. Values for these parameters varied with type of variants. Variants V2, V3 and V7 exhibited higher activity of antioxidant enzymes and had high accumulation of proline and total alkaloids. Conclusion: The variants V2, V3 and V7, having higher estimates for these parameters than that of parental variety which indicates their better survival/adaptive potential against salt stress condition and in context of salt tolerant may be utilized in genetic improvement programme of C. roseus.
Keywords: Antioxidant enzymes; Variants; Catharanthus roseus; Salt stress